(untitled) (Journal of the Asiatic Society of Bangladesh, Humanities, 2024)
Operation Searchlight was a brutal, planned military operation carried out by the Pakistan army on 25th March 1971. It signified the beginning of Bangladesh’s Liberation War. The operation was deployed simultaneously throughout the province. Their main target was the provincial capital, Dhaka. One of their primary targeted places in Dhaka was the University of Dhaka (DU) Campus.It is estimated that around 4000 to 6000 were killed in Dhaka cityduring Operation Searchlight. Among them, around 300 were killed inside the DU campus.Operation Searchlight killing destroyed the academic situation of the university.During the war, the government and the DU administration tried to ensure normalcy inside the campus. On the contrary, Bengali nationalist students and teachers tried to prove that an abnormal situation prevailed inside the campus. Thus, a worse situation was created inside the campus. In that situation, most teachers were bound to join the university to save their lives and jobs. However, Bengali nationalist teachers were under surveillance and some of them received Shani and Jamdot’s letters. Some teachers were rusticated, some were removed from the Syndicate, and some were arrested. The trial of some teachers and students was also organized in their absence, and ultimately, they brutally killed ten teachers of DU on 14th December 1971.In that worst situation, only 30 to 50 students attended the class. At last, on 16th December, the Pakistan Army surrendered at the Race Course ground, which is adjacent to the DU campus. This article explores the academic situation of the DU campus during the Liberation War of Bangladesh. It also focuses on the miserable conditions and the different types of punishment of Bengali nationalist teachers and students that they had to endure at that time. JASBH, Vol. 69(2), 2024, pp. 203-221